Smoothing control strategy of wind and photovoltaic output power fluctuation by considering the state of health of battery energy storage system - Lamsal, Dipesh; Sreeram, Victor; Mishra, Yateendra; Kumar, Deepak (IET renewable power generation, 2019)
The output power of wind and photovoltaic (PV) systems contain fluctuations due to the intermittent nature of solar irradiance and wind speed. It is required to smooth the fluctuated power before supplying it to the grid. Here, a fuzzy-based discrete Kalman filter approach is proposed for smoothing output power fluctuations of the wind and PV generation systems using a battery energy storage system. The proposed approach incorporates the state of health of the battery as a feedback to not only obtain smooth output power but also improve the battery health by adaptively regulating the battery power. The effectiveness of the proposed approach is verified by evaluating the power fluctuation rates and performance indices.